2008
DOI: 10.4238/vol7-3gmr449
|View full text |Cite
|
Sign up to set email alerts
|

Bos indicus or Bos taurus mitochondrial DNA - comparison of productive and reproductive breeding values in a Guzerat dairy herd

Abstract: ABSTRACT. The observation of bovine mitochondrial DNA (mtDNA) polymorphisms allows the separation of American zebu cattle, according to its maternal lineage ancestry, into two groups: one with Bos indicus mtDNA and other with Bos taurus mtDNA. The aim of the present study was to determine the productive and reproductive differences between these two groups, in a Guzerat dairy herd. The genotyping of a sample of 56 animals allowed the categorization of most of the 3835 animals in the pedigree file. The producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…One of the T4-specific substitutions leads to an L380M mutation in the cytochrome b gene and the G1324A substitution in T1c1a1 causes a mutated rRNA. However, no differences have been found in production and reproduction traits between Brazilian Guzerat zebus carrying taurine mtDNA and those carrying indicine mtDNA [43]. Nonetheless, there is no a priori reason why mtDNA-encoded gene products cannot be involved in selection and contribute to traits relevant for adaptation or production, thus leading to geographic differentiation of mtDNA.…”
Section: Resultsmentioning
confidence: 99%
“…One of the T4-specific substitutions leads to an L380M mutation in the cytochrome b gene and the G1324A substitution in T1c1a1 causes a mutated rRNA. However, no differences have been found in production and reproduction traits between Brazilian Guzerat zebus carrying taurine mtDNA and those carrying indicine mtDNA [43]. Nonetheless, there is no a priori reason why mtDNA-encoded gene products cannot be involved in selection and contribute to traits relevant for adaptation or production, thus leading to geographic differentiation of mtDNA.…”
Section: Resultsmentioning
confidence: 99%
“…More recent Indian zebu genetic influence in New World populations is supported by several lines of evidence including mtDNA (Magee et al, 2002;Paneto et al, 2008), Y chromosome microsatellites (Giovambattista et al, 2000), and autosomal STR and SNP genetic markers (Liron et al, 2006;Egito et al, 2007;Achilli et al, 2009;McTavish et al, 2013). Interestingly, McTavish et al (2013) suggest that the zebu ancestry observed in New World cattle may have originated, in part, from the founding Iberian cattle of the Americas; however, the lack of zebu ancestry in Iberian cattle has led Decker and colleagues (2014) to refute this and propose that zebu introgression in the Americas occurred after the arrival of Iberian cattle in the New World.…”
Section: New World Cattle Display Genetic Ancestry From Multiple Indementioning
confidence: 91%
“…The percentage of animals with zebu mtDNA varies in Brazil from 37% in the Gir breed to 43% in the Nelore 61 and 69% in the Guzerat breeds. 90 As shown by the distribution of the indicine Y-chromosomes 41 and microsatellite analysis, zebu bulls were crossed in several South American Criollo populations. 60,[91][92][93] Today, Brazil holds the largest commercial cattle population worldwide, with 200 million heads.…”
mentioning
confidence: 99%